2016
DOI: 10.1177/0954408915578791
|View full text |Cite
|
Sign up to set email alerts
|

A smart prediction tool for estimating the impact strength of welded joints prepared by vibratory welding process

Abstract: Previous researches have been devoted to development of vibratory setup for inducing mechanical vibrations into the weld pool during welding process. The designed vibratory setup produces the required frequency with suitable amplitude and acceleration in terms of voltages. This helps in producing uniform and fine grain structure in the welded joints which results in an improvement in the mechanical properties of the weld pieces at heat affected zone. This paper presents the development of a smart prediction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…By varying the input parameters of the metal engravers like voltage, frequency and vibrational period the process is done and enhancement of properties are taken place. P.Govinda Rao., et.al., [7][8][9][10][11][12] introduced the new experimental setup for inducing mechanical vibrations through unbalanced weight's. By considering the input parameters like vibrating period for specimens and voltage of the vibromotor.…”
Section: Introductionmentioning
confidence: 99%
“…By varying the input parameters of the metal engravers like voltage, frequency and vibrational period the process is done and enhancement of properties are taken place. P.Govinda Rao., et.al., [7][8][9][10][11][12] introduced the new experimental setup for inducing mechanical vibrations through unbalanced weight's. By considering the input parameters like vibrating period for specimens and voltage of the vibromotor.…”
Section: Introductionmentioning
confidence: 99%
“…11 Rao et al proposed vibratory welding technique to improve the joint toughness. 12 Fatima et al studied dissimilar welding of austenitic stainless steel with low carbon steel and commented that dissimilar welding is difficult and good quality can be obtained selecting optimum parameters. 13 Literature indicates that many investigations were carried out on dissimilar welding between different stainless steels and low carbon steel, and successful joining with adequate strength is predominantly dependent on selection of suitable process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…proposed vibratory welding technique to improve the joint toughness. 12 Fatima et al. studied dissimilar welding of austenitic stainless steel with low carbon steel and commented that dissimilar welding is difficult and good quality can be obtained selecting optimum parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed Metallurgical analysis has been performed in [19,20]. From the micro structural evolution it has been found that grain refinement occurs during random vibrations process.…”
Section: Variation In Metallurgical Propertiesmentioning
confidence: 99%
“…Compared to above said techniques, vibratory assisted welding has advantages such as economic, flexibility in use, pollution free and less manufacturing time [18]. Due to these special characteristics, vibratory welding techniques have been implemented effectively with varying degree of success [19][20][21]. Even though, the effect of vibratory parameters on mechanical properties of weldments is still a remaining question mark to the researchers.…”
Section: Vibratory Weldingmentioning
confidence: 99%